TO THE PROBLEM OF STUDYING THE SKILLS AND SKILLS OF SELF-SERVICE IN CHILDREN WITH SEVERE DEGREE OF MENTAL DEFECT IN A SPECIALIZED CHILDREN'S HOUSE (Education in the 21st Century, 2023)
It is known that a severe degree of mental retardation significantly complicates all types of activities of these children, including in the sphere of self-service. In the conditions of a specialized orphanage, the problem of the formation and development of self-service skills in children with a severe degree of mental retardation becomes somewhat more complicated. First of all, this is due to the fact that these children, like other pupils of these institutions, are constantly under the excessive care of nannies, educators and teachers, and self-service issues fade into the background.   Therefore, the study of self-service skills in children with severe mental retardation in a specialized orphanage and the search for effective means, methods and special pedagogical conditions for their use will become the basis for the formation and development of self-service skills and abilities in these children, correction and prevention of many self-service disorders.    At the same time, in the special scientific and methodological literature, insufficient attention is paid to the formation and development of skills and abilities of self-care in children with severe mental retardation, especially in these children of a specialized orphanage. However, the solution of this problem is very important for these children in their daily lives.  Thus, it becomes obvious that the importance of the problem under consideration, its insufficient knowledge and development determine the relevance of this study, its theoretical, practical and social significance.   The article analyzes the results of a study by special teachers of the problem of the formation and development of self-service skills in children with a severe degree of mental retardation, especially in these children of a specialized orphanage․ Based on the study of the results of the study of foreign and domestic specialists of the issues under consideration, a theoretical analysis, conclusions and recommendations are made.